PSYCHOLOGIST-PEDAGOGICAL PREREQUISITES AND REGULARITIES OF EFFECTIVE MANAGEMENT STUDENT PERSONALITY DEVELOPMENT in EDUCATIONAL PROCESS - Yu.V. Reva (Academy of Cognitive and Natural Sciences, 2022)
The article deals with psychological and pedagogical preconditions and original laws of governing the effective development of pupil's personality in the process of education.